2021
DOI: 10.1111/phor.12364
|View full text |Cite
|
Sign up to set email alerts
|

Automated calibration of smartphone cameras for 3D reconstruction of mechanical pipes

Abstract: This paper outlines a new framework for the calibration of optical instruments, in particular smartphone cameras, using highly redundant circular black‐and‐white target fields. New methods were introduced for (i) matching targets between images; (ii) adjusting the systematic eccentricity error of target centres; and (iii) iteratively improving the calibration solution through a free‐network self‐calibrating bundle adjustment. The proposed method effectively matched circular targets in 270 smartphone images, ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…SfM can provide 3D reconstruction up to an arbitrary scale factor only if an initial estimate of the IOPs along with the appropriate camera model are known a priori 4 . In [26], it was observed that SfM performed using initial IOPs obtained from laboratory pre-calibration, outperformed that obtained from exchangeable image file (Exif) for pipe reconstruction from smartphone cameras. Hence, in this manuscript, the smartphone cameras are pre-calibrated using the methods provided in [26,27].…”
Section: Dense 3d Reconstruction From Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…SfM can provide 3D reconstruction up to an arbitrary scale factor only if an initial estimate of the IOPs along with the appropriate camera model are known a priori 4 . In [26], it was observed that SfM performed using initial IOPs obtained from laboratory pre-calibration, outperformed that obtained from exchangeable image file (Exif) for pipe reconstruction from smartphone cameras. Hence, in this manuscript, the smartphone cameras are pre-calibrated using the methods provided in [26,27].…”
Section: Dense 3d Reconstruction From Imagesmentioning
confidence: 99%
“…In [26], it was observed that SfM performed using initial IOPs obtained from laboratory pre-calibration, outperformed that obtained from exchangeable image file (Exif) for pipe reconstruction from smartphone cameras. Hence, in this manuscript, the smartphone cameras are pre-calibrated using the methods provided in [26,27].…”
Section: Dense 3d Reconstruction From Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithm 1 requires an estimate of the interior orientation parameters (IOPs) of the camera, c, and P. This initial estimate can be obtained from pre-calibration [8,9], manufacturer's specifications, or the Exchangeable Image File (EXIF). In addition, it is possible to use Algorithm 1 to help correct camera positions in applications involving tracking spheres using cameras.…”
Section: 4mentioning
confidence: 99%
“…A pre-calibrated Huawei P30 mobile phone camera was used to acquire thirty-two 4K images of the spherical target. The calibration of the smartphone camera was performed using the method and IOPs presented in [9]. The position and orientation of the camera for each image view (exterior orientation parameters) were estimated automatically (independent of the spherical target's center) using COLMAP [11], a reliable open source structure-from-motion [12] software.…”
Section: Data Collection and Validationmentioning
confidence: 99%